Radiation dose constraints for organs at risk in neuro-oncology; the European Particle Therapy Network consensus. Issue 1 (July 2018) - Lambrecht, Maarten; Eekers, Daniëlle B.P.; Alapetite, Claire; Burnet, Neil G.; Calugaru, Valentin; Coremans, Ida E.M.; Fossati, Piero; Høyer, Morten; Langendijk, Johannes A.; Méndez Romero, Alejandra; Paulsen, Frank; Perpar, Ana; et al.
Abstract: Purpose: For unbiased comparison of different radiation modalities and techniques, consensus on delineation of radiation sensitive organs at risk (OARs) and on their dose constraints is warranted. Following the publication of a digital, online atlas for OAR delineation in neuro-oncology by the same group, we assessed the brain OAR-dose constraints in a follow-up study. Methods: We performed a comprehensive search to identify the current papers on OAR dose constraints for normofractionated photon and particle therapy in PubMed, Ovid Medline, Cochrane Library, Embase and Web of Science. Moreover, the included articles' reference lists were cross-checked for potential studies that met the inclusion criteria. Consensus was reached among 20 radiation oncology experts in the field of neuro-oncology. Results: For the OARs published in the neuro-oncology literature, we summarized the available literature and recommended dose constraints associated with certain levels of normal tissue complication probability (NTCP) according to the recent ICRU recommendations. For those OARs with lacking or insufficient NTCP data, a proposal for effective and efficient data collection is given. Conclusion: The use of the European Particle Therapy Network-consensus OAR dose constraints summarized in this article is recommended for the model-based approach comparing photon and proton beam irradiation as well as for prospective clinical trials including novel radiation techniques and/or modalities.